Effect of surface conditions on internal oxidation and nitridation of HVOF MCrAlY coatings - Chen, H; McCartney, D.G.; Voisey, K.T. (Taylor & Francis, 2015)
This study deals with the isothermal oxidation behaviour of high velocity oxy-fuel sprayed MCrAlY coatings. Both free-standing coatings and coatings attached to IN738 and CMSX4 substrates undergo isothermal oxidation at 1100°C for up to 100h. The effect of surface conditions (as-sprayed and polished) has been investigated. Scanning electron microscopy and energy dispersive X-ray analysis were used to characterise the details of oxidation behaviour. The results have shown that both surface conditions and substrate type have a pronounced effect on oxidation behaviour. Extensive internal oxidation and nitridation is observed for polished coatings on Inconel 738 and is attributed to the combined effects of titanium diffusion from the substrate and enhanced surface diffusion due to polishing.